Journal of Human Sport and Exercise - 2019 - Spring Conferences of Sports Science 2019
DOI: 10.14198/jhse.2019.14.proc4.74
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic modulation and association with the performance in a jump test in university Colombian players of rugby seven

Abstract: It has been observed that training influences modulation of autonomic activity and it can be represented in Heart Rate Variability (HRV). Evaluation of HRV can be useful to obtain information about the internal load to which an individual is being subjected, in order to adjust training loads, either with the aim of increasing sports performance or to prescribe an adequate load to improve specific qualities for the sport. Therefore, the purpose of this study was to evaluate the behaviour of autonomic modulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…The result showed quicker HR recovery after exercise in the rugby players. (10). This study also supported our results which concluded faster heart rate recovery in Badminton playing individuals.…”
Section: Resultssupporting
confidence: 90%
“…The result showed quicker HR recovery after exercise in the rugby players. (10). This study also supported our results which concluded faster heart rate recovery in Badminton playing individuals.…”
Section: Resultssupporting
confidence: 90%
“…All volunteers attended the Exercise Physiology laboratory at the Institución Universitaria Escuela Nacional del Deporte to perform an autonomic function test [18]. It was carried out in a closed room with a temperature between 22 • C and 24 • C and a relative air humidity of 50-60%.…”
Section: Autonomic Function Test and Recording Of Rr Interbeat Intervalsmentioning
confidence: 99%